Assessment of Oxygen Demand and Antibiotic Resistant Citrobacter spp. in the Bagmati River - Adhikari, Sakar; Adhikari, Sanot; Dhungana, Sudarshan; Singh Thapa, Prakash; Ghimire, Bindu (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To correlate the Oxygen demand with antibiotic resistant Citrobacter species in Bagmati river. Methods: A Cross-sectional study was conducted from May to August 2025 at the Department of Microbiology, Tri-Chandra Multiple Campus, Kathmandu. Fifteen water samples collected in duplicate were examined for biological oxygen demand (BOD), dissolved oxygen (DO), most probable number (MPN) counts and presence of antibiotic resistant Citrobacter species. The correlation analysis was conducted using Exploratory software version 6.10.3.1. Results: The MPN count of total coliforms was lowest at the upstream site (4 MPN/100 mL), and peaked downstream (35,000 MPN/100 mL). This was accompanied by a decline in DO (8.7, 4.2, and 1.2 mg/L) and an increase in BOD (0.1, 250.8, and 425.4 mg/L). Citrobacter appeared as pink, non-metallic colonies on EMB agar, and 394 isolates were confirmed biochemically. Among these, 100% were resistant to ampicillin (penicillin) and 99 % (390/394) toward erythromycin (macrolide), while resistance to cefotaxime (68%), amikacin (53%,aminoglycoside), ciprofloxacin (49%, fluoroquinolone), and chloramphenicol (44%, phenicol) was also recorded. Positive correlation (r = 0.835, p< 0.05) was observed for presence of Citrobacter and BOD and whereas negative correlation (r= -0.85, p<0.05) was observed for presence of Citrobacter and level of DO. Conclusion: The increase in BOD and decrease of DO in the downstream region and its correlation with the presence of antibiotic resistant Citrobacter species signifies polluted water as contributor to antibiotic resistant coliform.